Novel polyesters based on nitrogen-containing heterocycles: synthesis and research - Sugralina, L.M.; Omasheva, A.V.; Salkeeva, L.K.; Olzhabayeva, A.S.; Minayeva, Ye.V.; Taishibekova, Ye.K.; Salkeeva, A.K.; Baikenova, G.G. (KSU Publ., 2018)
The article presents the results of studies carried out at assembling two branches of science such as the chemistry of heterocyclic compounds and the chemistry of step-growth polymerization. 2,4-Dimethyl-3,5- diethoxycarbonylpyrrole (Knorr pyrrole) was synthesized by a series of successive transformations. 2,4-Dimethylpyrrole-3,5-dicarboxylic acid was obtained by Knorr pyrrole hydrolysis, optimal conditions for reaction were chosen. The process was shown to be completed within an hour and a half in an alcoholalkaline medium. A new polyester based on 2,4-dimethylpyrrole-3,5-dicarboxylic acid and ethylene glycol was synthesized by a polyesterification reaction. The physicochemical characteristics of the polymer obtained were established. Light-scattering method was used to determine the mass-average molar mass of the polyester, which turned out to be equal to 5263. The good convergence of the data calculated and the reproducibility of the experiment for determining the turbidity of dilute polymer solutions by turbidimetric method indicates the reliability of the results. Analysis of the structure and physical and chemical properties of the polymer synthesized suggests that a polyester based on 2,4-dimethylpyrrole-3,5-dicarboxylic acid and ethylene glycol can be used as a component of alkyd resins potentially possessing biological activity.
Азотқұрамды гетероциклдердің негізіндегі жаңа күрделі полиэфирлер: синтезі жəне зерттелуі
Новые сложные полиэфиры на основе азотсодержащих гетероциклов: синтез и исследование
Keywords: Knorr pyrrole; 2,4-dimethylpyrrole-3,5-dicarboxylic acid; polyesterification; polyester; turbidimetry